Effects of a Neonatal Supportive Positioning Training Video Program for Preterm Infants on the Knowledge and Performance of Nurses in Neonatal Intensive Care Units - Hyun Jin Moon; Kyung Sook Cho; Mi Young An; Dong Woo Son (Elsevier, 2022)
Summary: Purpose: The purpose of this study is to develop and apply a neonatal supportive positioning (NSP) training video program for premature infants, using a position support mat for nurses in neonatal intensive care units (NICUs), and to verify its effect on nurses' performance. Methods: Thirty-five NICU nurses were included in the study. For the pre-test, preliminary check-ups were conducted, questionnaires about NSP knowledge on preterm infants were distributed, and NSP performance using neonatal dolls were video recorded for each participant. PowerPoint presentations and videos were used to educate participants on NSP. Furthermore, a 20-minute one-on-one training session was conducted using an NPS kit. Two weeks after the training, we repeated the process of distributing questionnaires about NSP knowledge and recording nurses' performance videos using neonatal dolls. Questionnaires and videos collected before and after the training were compared. Results: After NSP training, the mean knowledge score of the participants improved significantly from 23.71 ± 3.62 to 29.51 ± 2.29 (Z = −5.09, p < .001). The performance score for postural supportive positioning was 38.03 ± 7.46 before training and 80.06 ± 9.85 after receiving training, indicating a high-performance score after NSP training (Z = −5.16, p < .001). Conclusion: Our NSP training video program increased nurses' NSP knowledge and performance. Continuous training NICU nurses on NSP, using a standardized training video program, can help improve the care of premature infants.